Risk Management Framework Design Based on ISO 31000 and SCOR Model - Rachmadhani, Mirga Maulana; Immawan, Taufiq; Mansur, Agus; Choi, Wonsik (Universitas Ahmad Dahlan, 2023)
In every large, medium and small industrial enterprise, risks must occur in the business process. The study conducted at one of the small medium enterprise (SME) in the Bantul, Yogyakarta. It begins with the fact that obstacles that often occur are delays in delivery, product damage, and also other obstacles. Hence, those are the reasons of this study conducted. Further, the risk management framework has an important role in reducing these problems. The approach used ISO 31000 method and the SCOR Model in making a proposed framework to improve risk management performance. Based on the proposed framework that has been made, the risk identification process in Rajut Bamboo has 32 risks in its business processes. The risk mitigation proposal is carried out on seven risks in the high-risk category. The risk mitigation results are obtained in the risk codes (D3) unfinished product and absence of SOP, (M2) quality control takes a long time, (P5) unplanned overhead costs, and (A1) products in storage are damaged or lost, thus it showed down to medium risk category, then the risk codes (D9) expensive packaging material costs, (D2) order time exceeds the specified time, and (M6) no mitigation planning, thus it showed down to low-risk category.